Pengaruh Pemahaman Teori Dasar Investasi, Modal Minimal, Dan Motivasi Terhadap Minat Berinvestasi Pada Generasi Milenial Area Surabaya Gresik - Dewi Putri Rahmawati; Bambang Karnain; Achmad Daengs GS; Sugiharto Sugiharto; I Gede Wiyasa (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The purpose of this study was to determine the effect of understanding the basic theory of investment, minimum capital and motivation on the millennial generation's interest in investing in the capital market. The millennial generation in this study focuses on young investors, aged between 17 to 35 years who live in Surabaya and Gresik and have active investment accounts of 50 people. The type of research used is quantitative. Information was collected through a questionnaire. The analytical method used is descriptive analysis, validity analysis, reliability analysis, multiple linear regression analysis, normality, hypothesis testing (T test and F test) and deretmination coefficient (R²). The results of the study show that the variable knowledge of basic investment theory results from t count > t table (2.138 > 2.012) and results t count > t table minimum capital variable (2.887 > 2.012) meaning that these two variables have a positive and significant effect on millennial generation investment interest in the capital market. While the motivational variable results t count > t table (-0.085 > -2.012) is negative, meaning that the motivational variable does not significantly influence the interest in investing in the millennial generation. From the results of the multiple regression test, the results are Y=4.095+ 0.203X1+ 0.653X2+ (-0.10X3)+ 0.363. The results of the F test obtained F count > F table (26.933 > 2.81).